Utilization of Polislidae Wasp Venom as Potential New Insect Drugs in the R&D of Wellness Industry - Liu, Heng; Gao, Pengfei; Wu, Xiumei; Yang, Zizhong; Liu, Weihong; Stöckigt, Joachim; Zhang, Chenggui; Zhao, Yu (International Journal of Biotechnology for Wellness Industries, 2013)
The Polislidae wasp, one species of omnivorous social insects mainly living in the bush or under the leaves. The wasp has a venom sac in its tail, and the venom secreted by a sting can cause a series of body reactions and diseases. Multiple organ failure could be the outcome of wasp sting, if timely treatment or rescue has not been performed. Based on published reports on wasp sting related to medical concerns in recent years, this review summarizes the symptoms caused by wasp sting and corresponding mechanisms of actions. The medical application and relational utilization of the title insect is suggested derived from findings of the systematic review. Furthermore, we herewith sketch the perspectives of R&D on the venom of Polislidae wasp. It is expected to afford comprehensive references and be useful for broader study on the natural components and pharmacological effects of wasp venom.